High perirenal fat thickness predicts a greater risk of recurrence in Chinese patients with unilateral nephrolithiasis - Haichao Huang; Shi Chen; Wenzhao Zhang; Tao Wang; Peide Bai; Jinchun Xing; Huiqiang Wang; Bin Chen (Renal Failure)
Introduction The aim of this study was to evaluate the association between recurrence-free survival (RFS) and perirenal fat thickness (PFT) in a cohort of Chinese population with unilateral nephrolithiasis.Methods We retrospectively reviewed the medical records of 81 patients with unilateral nephrolithiasis in our center from January 2019 to June 2019. PFT measured on computed tomography (CT) scans was evaluated. Kaplan-Meier curves and log-rank tests were used to assess significant differences in RSF between high-PFT and low-PFT groups within sexes. Univariable and multivariable Cox regression analyses were used to evaluate the potential risk factors for renal stone recurrence.Results High PFT was significantly associated with high BMI and hyperlipidemia (p = .003 and.047, respectively). The PFT of stone-bearing kidney was significantly greater than PFT of non-stone-bearing kidney (0.77 ± 0.60 cm vs. 0.67 ± 0.58 cm, p = .002). During the follow-up periods (median 31 months), 21 (25.9%) patients experienced ipsilateral renal stone recurrence. In addition, Kaplan–Meier survival curves showed that patients with low PFT had a significant better RFS than those with high PFT (p = .012). In the univariable Cox analyses, male sex and high PFT were significantly associated with a poor RFS (p = .042 and .018, respectively). Moreover, both male sex and high PFT retained significance in the multivariable analyses (p = .045 and .020, respectively).Conclusions Our findings suggested that PFT is a noninvasive and feasible parameter, which may help in the risk stratification of renal stone recurrence in the follow-up periods.